Allosteric crosstalk in modular proteins: Function fine-tuning and drug design - Suman Abhishek; Waghela Deeksha; Krishnapura Ranganatha Nethravathi; Mehdi D. Davari; Eerappa Rajakumara (Computational and Structural Biotechnology Journal, 2023)
Modular proteins are regulatory proteins that carry out more than one function. These proteins upregulate or downregulate a biochemical cascade to establish homeostasis in cells. To switch the function or alter the efficiency (based on cellular needs), these proteins require different facilitators that bind to a site different from the catalytic (active/orthosteric) site, aka ‘allosteric site’, and fine-tune their function. These facilitators (or effectors) are allosteric modulators. In this Review, we have discussed the allostery, characterized them based on their mechanisms, and discussed how allostery plays an important role in the activity modulation and function fine-tuning of proteins. Recently there is an emergence in the discovery of allosteric drugs. We have also emphasized the role, significance, and future of allostery in therapeutic applications.